Luka kompetencyjna mistrzów w rzemiosłach budowlanych w świetle wyników projektu ENCORE - Andrzej Wojciech Stępnikowski; Michał Jan Ślusarczyk (Edukacja Ustawiczna Dorosłych)
This article summarises the results of the ENCORE project ‚Environmental education model for masters and stakeholders involved in construction and renovation’. The project aims to lay the foundation for standards of the changes in examination requirments standards by demonstrating the existence of a competence gap among craftsmen. This gap is related to their awareness of the new challenges posed to them by the Renovation Wave. In this article, based on the conclusions drawn from our own research, we present a initial proposal for changing the examinational requriments in building crafts.